2013
DOI: 10.1063/1.4860949
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport properties of Si-doped hexagonal boron nitride epilayers

Abstract: The suitability of Si as an n-type dopant in hexagonal boron nitride (hBN) wide bandgap semiconductor has been investigated. Si doped hBN epilayers were grown via in-situ Si doping by metal organic chemical vapor deposition technique. Hall effect measurements revealed that Si doped hBN epilayers exhibit n-type conduction at high temperatures (T > 800 K) with an in-plane resistivity of ∼12 Ω·cm, electron mobility of μ ∼ 48 cm2/V·s and concentration of n ∼ 1 × 1016 cm−3. Temperature dependent resistivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…This was achieved via the use of square shaped sample geometry with triangular ohmic contacts fabricated on the four corners of the sample. [18][19][20] The microscope image of a fabricated h-(BN) 1-x (C 2 ) x alloy (x = 0.032) sample with ohmic contact (Ni/Au bilayers) geometry employed is shown in Fig. 4(a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was achieved via the use of square shaped sample geometry with triangular ohmic contacts fabricated on the four corners of the sample. [18][19][20] The microscope image of a fabricated h-(BN) 1-x (C 2 ) x alloy (x = 0.032) sample with ohmic contact (Ni/Au bilayers) geometry employed is shown in Fig. 4(a).…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of the contact size (c) to the sample length scale (L) is about 1/7.5, a configuration which is expected to provide a high confidence in the measured carrier type. 18 Ohmic contact processing procedures were adopted from those developed from pure h-BN epilayers 20 and the ohmic behavior is evident based on the linear I-V characteristic shown in Fig. 4(b).…”
Section: Resultsmentioning
confidence: 99%
“…He et al [43] showed, via Hall effect and temperature-dependent resistivity measurements, n-type conduction with a low resistivity at room temperature and two shallow donor levels at high temperature of about 800 K when the Si occupies the B site. On the other hand, Majety et al [45] reported a deep donor level of about 1.20 eV using the same technique and concluded that Si-doped h-BN is not suitable for room temperature device applications. Inspired by the experimental realization of Si-doped h-BN monolayers, [44,45] a systematic study of the physical properties of various possible Si atomic configurations will be interesting.…”
Section: Introductionmentioning
confidence: 99%
“…[15,[42][43][44][45][46][47] Using DFT methods, Liu et al [47] revealed that the Si impurity prefers the B site, but as opposed to C, it severely deforms the h-BN structure preserving the sp 3 -like bonding.…”
Section: Introductionmentioning
confidence: 99%
“…As a n-type dopant for sp 2 -BN sulphur (S) found to be suitable [24]. However, common group 13-N n-type dopant silicon (Si), is found to be a deep donor that needs temperature of 800 °C to be activated and thus is not suitable for room temperature applications [26]. Similarly as for 13-nitrides, Mg has been successfully employed as a p-type dopant for BN [27].…”
Section: Properties and Applications Of Sp 2 -Bnmentioning
confidence: 99%